Free vibration of agglomerated carbon nanotube reinforced composite sandwich beam using an enriched finite beam element - Tran, Thom Thi; Bui Thi Thu, Hoai; Nguyen Dinh, Kien (Vietnam Journal of Science and Technology, 2025)
Free vibration of carbon nanotube reinforced composite (CNTRC) sandwich beams, taking into account the effect of CNT agglomeration, is studied using an efficient beam element. The sandwich beams consist of three layers, a homogeneous core and two agglomerated CNTRC face sheets with material properties being estimated by the Eshelby-Mori-Tanaka approach. Based on the trigonometric shear deformation theory, a finite beam element is formulated and used to construct the discretized equation of motion for the beams. To improve the efficiency of the element, hierarchical functions are employed to enrich the conventional Lagrange and Hermite interpolation functions. The numerical investigation shows that the formulated beam element is efficient, and it is capable to give accurate natural frequencies by using a small number of elements. It is also foundation the frequencies of the beams are significantly influenced by the CNT agglomeration, and the increase of CNT reinforcement may not be useful for the beam with severe CNT agglomeration. A parametric study is carried out to investigate the effects of the agglomeration, the volume fraction of CNTs as well as the layer thickness ratio on the vibration of the sandwich beams.